(untitled) (Bangladesh Journal of Botany, 2023)
Kundru (Coccinia indica) and Kikar (Acacia nilotica) are well known for their uses in Indian ayurveda to treat diabetes. Although the two plants are well known for their medicinal properties, not much literature is available regarding their nutritional composition. The present study reports the nutritional composition and antioxidant activity of fruits of the two plants. Significant (P ≤ 0.05) differences were observed in ash and crude protein content of Kikar (2.47 and 17.30 g/100 g, respectively) and kundru (1.97 and 7.54 g/100 g, respectively). Resistant starch in Kundru and Keekar was 0.52 and 0.12 g/100g, respectively. In-vitro protein digestibility was significantly (P≤0.05) higher in Kikar (35.43 %). Total phenol, flavonoids, DPPH scavenging activity and ferric reducing antioxidant power was observed to be significantly (P ≤ 0.05) higher in Kundru (65.13 mg GAE/100 g, 80.04 mg RE/100g, 75.14 mg TE/100 g and 68.95 mg TE/100 g, respectively) as compared to Kikar (51.05 mg GAE/100 g, 25.29 mg RE/100 g, 63.84 mg TE/100g and 35.22 mg TE/100g, respectively). Bangladesh J. Bot. 52(2): 389-394, 2023 (June)